Metode Pembelajaran Pendidikan Agama Islam Pada AnakTunagrahita Kelas 12 Di Smalb Negeri Surakarta Tahun 2016 - Nafisah, Nuhla Fauziyyatun; , Istanto, S.Pd.I., M.Pd (2017)
The background of this study is the importance of an education, including the learning of Islamic Education, for all citizens who are Muslims. No exception for retarded children who have mental disabilities. These limitations do not become a barrier for children with intellectual challenges in terms of education. In fact, teaching children with intellectual challenges can not be equated with normal children in general, certainly in providing learning teachers must use a special method for the purpose that the educational process can be achieved best. Issues that will be discussed in the present study is what learning methods are used in the teaching of Islamic Education for persons with Tunagrahita (mental retardation) in SMALB class 12 in Surakarta 2016 The purpose of this study is to determine and describe the methods used in the study of Islamic education in the classroom 12 of SMALB Negeri Surakarta. This is important because seeing the problems faced by children with intellectual challenges in the learning process. They experienced difficulties for they have below average intelligence, so that the retarded child in the learning process requires a special approach. This research is a field research where in activities carried out in a particular community by visiting the direct target object. The methods used in gathering date are observation, documentation, and in-depth interviews. While the method of data analysis is done in a descriptive way, that disclosure of the circumstances as they are. From the results of this study it is concluded that the teaching methods of Islamic education for retarded children using augmentation, lectures, demonstrations, rote, direct practice and methods of drill or exercise. In addition, teachers in presenting material to students use easily understandable language for learners and deliver repeatedly until students really understand the material presented by the teacher, then the teacher should be able to create a classroom atmosphere to entertain the students and make students comfortable. The results of the study of Islamic education show their positive impact for children with intellectual challenges in the form of a significant change towards better understanding or behavioral change of learners.